Infrared Spectra and Photochemistry of Matrix-Isolated Pyrrole-2-carbaldehyde - Giuliano, Barbara Michela (2010)
Monomeric pyrrole-2-carbaldehyde (P2C) was isolated in low-temperature argon and xenon matrices, and its UV-induced photochemistry was studied. The structures of the reagent as well as the reaction photoproducts were characterized by FTIR spectroscopy. Interpretation of the experimental results was assisted by theoretical calculations carried out at the MP2 and DFT (B3LYP) levels with the 6-311++G(d,p) basis set. The compound can assume two conformations, cis and trans, regarding the orientation of the N−C−C═O dihedral angle. The cis form is the conformational ground state, being more stable than the trans by ca. 15 kJ mol−1. The relative stability of the two conformers was analyzed based on the comparison of their structures and using the natural bond orbital method. In agreement with the calculations, only the signature of the cis conformer was found in the experimental FTIR spectra of matrix-isolated P2C monomers. UV irradiation (λ > 235 nm) readily converts the cis-P2C into the trans-P2C form, and a photostationary equilibrium is established where the [cis]/[trans] ratio is ca. 3.3:1 in both Ar and Xe. Upon prolonged irradiation, P2C slowly undergoes photolysis to [pyrrole + CO]. In matrices, pyrrole and CO form associates of different geometry, which could be characterized based on their vibrational signatures.